KAJIAN ADAPTASI BEBERAPA VARIETAS UNGGUL JAGUNG DI KABUPATEN MALUKU BARAT DAYA (MBD) - Sheny Sandra Kaihatu; Florentina Watkaat (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2015)
Adaptation study of hybrid maize varieties and improved varieties do subdistrict Wonreli Southwest Maluku district from September to December 2012. Study using a randomized block design repeated 3 times and farmers as replicates. Varieties tested is the Bima-3, Bima-4, Bima-5, Srikandi kuning, Lamuru, Lagaligo and Lokal MBD as a comparison. Fertilization is done drill, a distance of 5-7 cm from the plant, fertilizer dose of 300 kg urea, 200 kg SP-36, 100 kg of KCl and 1-2 t.ha-1manure. Urea fertilizer done twice, is 100 kg urea and entire SP36 and KCl at the age of 7-10 plants hst and residual urea 200 kg administered at 30 dap. Parameters observed plant height at harvest, High cob, cob diameter, cob length, number of rows/cob, number of grains / row, weight of 1000 seeds and Yield per hectare. The results of the study showed that of the varieties tested turned out varieties Bima-5 higher result of (6.7 t.ha-1) and the lowest result is Lokas MBD ( 5.7 t.ha-1).